The training in social and solidarity economy. Analysis of the university offer in Spain - Flores Ruiz, David; Guzmán Alonso, Carmen; Barroso González, María de la O (REVESCO. Revista de Estudios Cooperativos, 2015)
This research analyses the importance of the training for the promotion of the social economy in two ways: 1) focusing on the characteristics of the educational offer of Social Economy and 2) analyzing its differences regarding to those studies from the Management, entrepreneurship, and innovations areas. To this aim, it is carried out as a first step a literature review of the contributions that study the relationships that can exist between the education and Economy. Then, being based on this previous analysis, we already center our research on the Social Economy sector and its relations with the education system. To get this objective, it has been developed a database that includes all the postgraduate titles related to the Economics area. Likewise, a questionnaire has been designed with the aim of characterize the training in social Economy. As a conclusion, it is obtained that the training in social economy in postgraduate studies in the Spanish Universities is very poor. On the other hand, there are significant differences between Social Economy degrees and Business Management, entrepreneurship and innovation degrees with regard to different aspects such as: values to transmit, competencies, skills, the way of understanding the Economy, etc. Based on these conclusions, different recommendations are proposed in order to promote and boost this other way of doing Economy through the training and education in postgraduate studies.
Keywords: Economic Studies; Social Economy; Higher Education; postgraduate studies; Social Sciences.